Comparative characteristics of osteosynthesis techniques in patients with comminuted diaphyseal femoral fractures - A. P. Barabash; S. P. Shpinyak; J. A. Barabash (Travmatologiâ i Ortopediâ Rossii, 2013)
The comparative analysis of the results of the surgical treatment of 130 patients with closed comminuted unilateral diaphyseal femoral fractures, including assessment of anatomic functional outcomes of treatment according to the technique of the standardized investigations in traumatology and orthopedy and determination of quality of life according to SF-36 method is carried out. Osteosynthesis with the help of external fixation devices was performed in 36 patients, intramedullary interlocking osteosynthesis - in 57 patients, compression plating - in 37 patients. Level of anatomic functional rehabilitation of the patients in the early postoperative period made up 69-79 %, 6 months later increased up to 74-92%, and after the expiration of 12 months the level of rehabilitation reached 85-99%. During the treatment quality of life concerning physical component was within the limits from 36,8 up to 55,5 %, and concerning mental component - 54,3-60,8 %. After the expiration of a year increase in the parameters of physical and mental components up to 55,7 - 59,8 % and 57,2-65,8 % is detected respectively. In the group where the transosseous osteosynthesis technique was applied we got 93,7-95 % of positive outcomes, with the average disability period of 212,3±18,1 days. In 47,2 % of cases the following complications are observed: knee contracture - 7; inflammation of the soft tissues located near the transosseous fixators - 5 (13,9%); shortening of the limb less than 5% of its length - 3; false joint formation - 1; fracture union with formation of varus deformity in the femoral bone - 1. When using intramedullary interlocking osteosynthesis we had positive results in 96,5 % of cases, with the average period of disability 176±17,8 days. In 10,5 % cases the following complications are observed: suture sinus - 1(1,75 %); femoral osteomyelitis - 1; break of the design - 1; false joint formation - 1; knee contracture - 1; shortening of the limb less than 5% of its length - 1. The best outcomes of the surgical treatment (up to 100 %) were observed in cases when compression plating with LCP with fixation of no less than 57 % of the length of each fragment was performed. Complications in the form of a knee joint contracture were observed in 13,5% of patients.